Fault modelling and detection in power generation, transmission and distribution systems. Issue 16 (1st December 2015) - Ali, Asghar; Khan, Abdul Qayyum; Hussain, Babar; Raza, Muhammad Taskeen; Arif, Muhammad
Abstract : The study discusses a model‐based fault diagnosis scheme for detection of faults in power systems. The fault models in power generating units (PGUs) and transmission and distribution networks (T&DN) have been derived in state space form. An observer‐based fault detection filter (FDF) has been used to detect these faults. Observer‐based FDF is used because of its simplicity, reliability and ease of implementation. A single machine infinite bus power system is considered wherein a synchronous generator is connected to a T&DN through a bus system. Actuator and sensor faults in PGU, and symmetric faults in T&DN have been modelled and simulated in Matlab/Simulink. The simulation results show that a fault, whenever occurs in the aforementioned parts of power systems, is detected using the knowledge of the faults models proposed in this work.